A monovalent selective cation separation membrane and a method for preparing the same
Patent Information
- Application Number
- CN202611205891.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-10-27
AI Technical Summary
然而,该方法制备的膜仍存在诸多难以忽视的问题
1、离子选择性与通量同步提升:在本申请方案中,选用第一交联剂为γ-缩水甘油醚氧丙基甲基二甲氧基硅烷或环氧基聚乙二醇作为第一交联剂,其自带的环氧端基可与含氨基类化合物的氨基高效发生开环反应,而γ-缩水甘油醚氧丙基甲基二甲氧基硅烷分子自带的柔性聚硅氧烷链段或环氧基聚乙二醇分子自带的柔性聚乙二醇链段均可调节交联网络刚性,为后续通道构筑提供均匀骨架;在此基础上,在第二交联剂的作用下构筑超薄选择性分离层(即改性层),精准调控表面电荷密度和孔径分布,结合原位构筑尺寸均一的锂离子专属通道,实现Li+/Mg2+分离系数高达18(较传统膜提升60%),优于现有商业膜,满足高效分离需求。
Smart Images

Figure CN122974141A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of functional polymer membrane materials, and mainly to a monovalent selective cation separation membrane and its preparation method. Background Technology
[0002] Ion exchange membranes, as polymeric materials with selective ion permeability, are core components of technologies such as electrodialysis, diffusion dialysis, and fuel cells, playing an irreplaceable role in seawater desalination, wastewater treatment, chemical purification, and energy conversion. However, with the increasing demands for precision and efficiency in ion separation from industrial production, traditional ion exchange membranes are struggling to meet the selective separation requirements under complex operating conditions, especially in the precise separation of monovalent and divalent cations, such as Li-ion extraction from salt lakes. + With Mg 2+ Separation of Na in the chlor-alkali industry + With Ca 2+ Separation and other processes have spurred a surge in the research and development of highly selective cation exchange membranes.
[0003] Currently, researchers both domestically and internationally have conducted extensive work on the preparation of highly selective cation exchange membranes, resulting in various technical approaches. For example, one approach involves constructing a charged layer on the membrane surface to achieve the separation of cations with different valence states using the Donnan repulsion effect; another is to control the membrane's pore structure to block the permeation of divalent cations through a sieving effect; and a composite modification strategy combining charge modification with pore size control is also employed. However, existing technologies still face many unresolved issues, limiting their industrial application.
[0004] Existing technology discloses a method for preparing a monovalent selective cation separation membrane based on the co-deposition of dopamine, polyethyleneimine, and chitosan. This method introduces a UV photoinitiator and chitosan to accelerate the deposition rate of the modified layer on the membrane surface. Simultaneously, chitosan connects the base membrane and the modified layer, improving membrane stability and pore size sieving effect without occupying ion exchange sites, maintaining good ion flux when separating monovalent and polyvalent cations. However, this technical route still has significant shortcomings that restrict its industrial application. First, the co-deposition process requires strict control of UV radiation intensity, time, and solution concentration. The process parameters are highly sensitive, and uneven thickness of the modified layer on the membrane surface is prone to occur during industrial scale-up, leading to large batch-to-batch fluctuations in membrane performance. According to relevant test data, the monovalent cation selectivity coefficient of the membrane at the pilot scale can deviate by ±12%, which is insufficient to meet the stability requirements of industrial production. Second, dopamine is prone to self-polymerization in alkaline environments. If the reaction conditions are not properly controlled, it can form random aggregates that block some pores on the membrane surface, thus reducing ion flux. Compared with traditional modified membranes, there is still room for improvement. Furthermore, although chitosan enhances the bonding force between the modified layer and the base membrane, it is prone to protonation and dissolution in acidic environments. When treating acidic brine, the long-term stability of the membrane remains a concern. After 80 days of continuous operation, the selective retention rate of monovalent cations drops to 68%, which cannot fully adapt to the complex and ever-changing industrial liquid environment.
[0005] Existing technology also discloses a method for the continuous industrial production of monovalent selective cation exchange membranes. This method constructs a selective layer on the surface of a cation exchange membrane by electrodeposition and cross-linking of polyethyleneimine, enabling continuous industrial production and improving the membrane's selective permeability to some extent. However, the membranes prepared by this method still have several significant problems. First, the membrane's long-term stability is insufficient. During long-term electrodialysis operation, especially in complex industrial environments such as high salt and strong acid / alkali conditions, the modified layer is prone to swelling and shedding, leading to a sharp decline in membrane selectivity. In practical industrial applications, some membranes using this technology show a monovalent cation selectivity retention rate of less than 70% after 60 hours of continuous operation, failing to meet the requirements for long-term stable operation in fields such as lithium extraction from salt lakes and brine refining. Second, the membrane resistance is high, resulting in significant energy loss. To ensure selectivity, the electrodeposited polyethyleneimine layer needs to reach a certain thickness, which undoubtedly increases the membrane resistance. Test data shows that the surface resistance of the membrane prepared by this patent is about 40% higher than that of the unmodified cation exchange membrane, leading to higher energy consumption during electrodialysis and increasing the cost of industrial production. Furthermore, the membrane has poor antifouling properties. The polyethyleneimine layer is rich in polar groups such as amino groups, which easily adsorb organic matter, colloids, and other impurities in the feed solution, causing membrane fouling. This further exacerbates the increase in membrane resistance and shortens the membrane's lifespan. When treating old brine from salt lakes containing organic matter, the membrane flux of the electrodialysis unit using this membrane decreased by more than 25% after 10 days of operation, requiring frequent cleaning and maintenance.
[0006] Therefore, existing technologies still need to be improved and developed. Summary of the Invention
[0007] In view of the shortcomings of the prior art, the purpose of this application is to provide a monovalent selective cation separation membrane and its preparation method, which aims to prepare a monovalent selective cation separation membrane with high selectivity, high ion flux, excellent acid and alkali resistance and stability by reacting amino-containing compounds with crosslinking agents.
[0008] The technical solution of this application is as follows: A method for preparing a monovalent selective cation separation membrane, comprising the following steps: Step (1): Mix deionized water, amino-containing compound, and first crosslinking agent to obtain a prepolymer solution; Step (2): The prepolymer solution is coated onto the surface of the cationic base membrane to carry out the first crosslinking reaction, thereby obtaining a primary crosslinked membrane; Step (3): Place the primary crosslinking membrane in a solution containing a second crosslinking agent to carry out a second crosslinking reaction, thereby obtaining the monovalent selective cation separation membrane; The first crosslinking agent is γ-glycidyl oxypropyl methyl dimethoxysilane or epoxy polyethylene glycol.
[0009] The method for preparing the monovalent selective cation separation membrane, wherein the mass percentage of the amino-containing compound in the prepolymer solution is 1.0%-1.2%; Preferably, the amino-containing compound is an amino-containing compound; Preferably, the amino-containing compounds include high molecular weight amino-containing compounds and low molecular weight amino-containing compounds; Preferably, the high molecular weight amino-containing compound has a molecular weight ≥5000 Da, and the low molecular weight amino-containing compound has a molecular weight range of <5000 Da. Preferably, the molecular weight of the high molecular weight amino-containing compound is 5000-100000 Da; Preferably, the molecular weight of the high molecular weight amino-containing compound is 10,000-100,000 Da; Preferably, the molecular weight of the low molecular weight amino-containing compound is ≤1800 Da.
[0010] The method for preparing the monovalent selective cation separation membrane, wherein the mass ratio between the high molecular weight amino-containing compound and the low molecular weight amino-containing compound is 1:1 to 1:4; Preferably, the high molecular weight amino-containing compound is one or a mixture of two of polyethyleneimine and chitosan; Preferably, the low molecular weight amino-containing compound is one or a mixture of two or more of triethylamine, ethylenediamine, and triethylenetetramine; Preferably, the high molecular weight amino-containing compound is polyethyleneimine, and the molecular weight of the polyethyleneimine is 9 kDa - 11 kDa; Preferably, the low molecular weight amino-containing compound is triethylenetetramine.
[0011] In the method for preparing the monovalent selective cation separation membrane, the mass percentage of the first crosslinking agent in the prepolymer solution is 0.70%–1.0%.
[0012] In the method for preparing the monovalent selective cation separation membrane, the mass percentage of the second crosslinking agent in the solution containing the second crosslinking agent is 0.1%–0.5%. Preferably, the second crosslinking agent includes any one or a combination of at least two of the following: aldehyde crosslinking agents, isocyanate crosslinking agents, silane crosslinking agents, metal chelate crosslinking agents, or natural polyphenol crosslinking agents. Preferably, the second crosslinking agent is an aldehyde crosslinking agent; Preferably, the second crosslinking agent is one or a combination of two or more of 3-chloropropionaldehyde, glutaraldehyde, glyoxal, formaldehyde or succinaldehyde; Preferably, the second crosslinking agent is butyraldehyde.
[0013] The method for preparing the monovalent selective cation separation membrane, wherein the reaction temperature of the first crosslinking reaction is 65℃-95℃ and the reaction time is 25 min-35 min.
[0014] Preferably, the reaction time for the second crosslinking reaction is 20 min - 25 min.
[0015] The method for preparing the monovalent selective cation separation membrane, wherein, in step (2), before the step of coating the prepolymer solution onto the surface of the cation-based membrane, the following steps are further included: The cationic membrane is pretreated; Preferably, the pretreatment process involves sequentially performing ultrasonic cleaning, sodium chloride solution immersion, and deionized water rinsing on the cationic membrane. Preferably, the cleaning solution used in the ultrasonic cleaning is deionized water or ethanol; Preferably, the sodium chloride solution soaking is performed in a sodium chloride solution with a mass ratio of 5%-10% for 24 h-48 h.
[0016] The method for preparing the monovalent selective cation separation membrane further includes the following steps after step (3): Step (4): Post-processing; Preferably, the post-processing involves immersing the monovalent selective cation separator in a sodium chloride solution, rinsing it with deionized water, and storing it while keeping it moist. Preferably, in step (4), the mass concentration of the sodium chloride solution is 5%-10%, and the soaking time is 24 h-48 h.
[0017] The method for preparing the monovalent selective cation separation membrane, wherein the cation-based membrane is a homogeneous cation-based membrane; Preferably, the cationic membrane is a polyolefin-based membrane, a polysulfone-based membrane, a polyethersulfone-based membrane, or a polyacrylonitrile-based membrane; Preferably, the cationic base membrane is a polyolefin base membrane or a polyethersulfone base membrane.
[0018] A monovalent selective cation separation membrane prepared by the above-described method.
[0019] Beneficial Effects: The monovalent selective cation separation membrane prepared in this application can meet the needs of separating cations of different valence states in fields such as salt lake resource development, heavy metal wastewater treatment, chemical raw material purification, selective electrodialysis, and fuel cells. Compared with existing technologies, this application has significant advantages in preparation process, performance stability, applicable scope, and cost control, providing an efficient and economical solution to the problem of selective separation of cations of different valence states under complex operating conditions, and has broad prospects for industrial application. Attached Figure Description
[0020] Figure 1 This is a SEM image of the monovalent ion selective cation exchange membrane provided in Embodiment 1 of the present invention at a magnification of 5000X.
[0021] Figure 2 This is a SEM image of the monovalent ion selective cation exchange membrane provided in Comparative Example 1 of the present invention at a magnification of 5000X.
[0022] Figure 3 This is a SEM image of the monovalent ion-selective cation exchange membrane provided in Comparative Example 2 of the present invention at a magnification of 5000X. Detailed Implementation
[0023] This application provides a monovalent selective cation separation membrane and its preparation method. To make the objectives, technical solutions, and effects of this application clearer and more explicit, the following provides a more detailed description. It should be understood that the specific embodiments described herein are merely illustrative of this application and are not intended to limit this application.
[0024] This application provides a method for preparing a monovalent selective cation separation membrane, comprising the following steps: Step (1): Mix deionized water, amino-containing compound and first crosslinking agent to obtain prepolymer solution.
[0025] In this application, the prepolymer solution includes deionized water, an amino-containing compound, and a first crosslinking agent.
[0026] The amino-containing compound is an amino-containing compound, which includes both high molecular weight amino-containing compounds and low molecular weight amino-containing compounds.
[0027] The high molecular weight amino-containing compound has a molecular weight ≥ 5000 Da. Preferably, the molecular weight of the high molecular weight amino-containing compound is 5000-100000 Da; more preferably, the molecular weight of the high molecular weight amino-containing compound is 10000-100000 Da. Further, the high molecular weight amino-containing compound can be one or a mixture of two of polyethyleneimine and chitosan.
[0028] Preferably, the high molecular weight amino-containing compound is polyethyleneimine, and the weight-average molecular weight of polyethyleneimine can be 9-11 kDa.
[0029] The molecular weight of the low-molecular-weight amino-containing compound is <5000 Da. Preferably, the molecular weight of the low-molecular-weight amino-containing compound is ≤1800 Da.
[0030] Furthermore, the low molecular weight amino-containing compound can be one or a mixture of two or more of triethylamine, ethylenediamine, and triethylenetetramine.
[0031] In this application, low-molecular-weight amino-containing compounds are used to penetrate into the micropores of the membrane material, effectively blocking non-selective defect channels. Simultaneously, high-molecular-weight amino-containing compounds form a stable structure through long-chain entanglement. The synergistic effect of these two compounds constructs transport channels with a pore size gradient, enabling Li... + (Hydration radius is 0.38 nm) and Mg 2+ Maximizing the difference in diffusion rates (with a hydration radius of 0.43 nm) is beneficial for achieving selective separation of monovalent ions.
[0032] The first crosslinking agent can be γ-glycidyl oxypropyl methyl dimethoxysilane or epoxy polyethylene glycol.
[0033] Preferably, the first crosslinking agent is γ-glycidoxypropylmethyldimethoxysilane. In step (1), by adjusting the mass fraction of the amino-containing compound and the first crosslinking agent, the reaction between the amino group of the amino-containing compound and the first crosslinking agent can be controlled, so that part of the amino group of the amino-containing compound undergoes a crosslinking reaction with the first crosslinking agent to form a stable crosslinked structure, while the other part of the amino group undergoes secondary crosslinking to form a selective separation layer.
[0034] Furthermore, in the prepolymer solution, the mass percentage of amino-containing compounds is 1.0%-1.2%, for example, 1.0%, 1.1%, 1.2%, but not limited to the listed values; other unlisted values within the range also apply. When the content of amino-containing compounds is too low, it can easily lead to incomplete reaction, resulting in visible pinhole defects on the film surface. When the concentration of amino-containing compounds is too high, it can easily lead to uneven coating, resulting in inconsistent thickness of the surface coating and causing localized stress concentration.
[0035] Furthermore, in the prepolymer solution, the mass ratio between high molecular weight amino-containing compounds and low molecular weight amino-containing compounds can be 1:1 to 1:4, for example, 1:1, 1:2, 1:3, and 1:4, but is not limited to the listed values; other unlisted values within the range are also applicable. Using the above ratio of high molecular weight amino-containing compounds and low molecular weight amino-containing compounds can give the monovalent selective cation separation membrane ion selectivity. If the ratio is too low, it may lead to insufficient modification; if the ratio is too high, it may lead to excessive densification.
[0036] Furthermore, in the prepolymer solution, the mass percentage of the first crosslinking agent is 0.70%-1.0%, for example, 0.70%, 0.75%, 0.80%, 0.85%, 0.90%, 0.95%, or 1.0%, but not limited to the listed values; other unlisted values within the range are also applicable. When the concentration of the first crosslinking agent is too low, unreacted active sites will swell and detach in water; when the concentration of the first crosslinking agent is too high, it will result in excessive crosslinking, leading to a loss of flexibility in the cationic base film.
[0037] Specifically, the process of step (1) can be as follows: High molecular weight amino compounds and low molecular weight amino compounds are mixed and dissolved in deionized water and stirred until transparent. Then, the first crosslinking agent is added to obtain a prepolymer solution.
[0038] Step (2): Coat the surface of the cationic base membrane with the prepolymer solution and carry out the first crosslinking reaction to obtain a primary crosslinked membrane.
[0039] In step (2), it is necessary to control the temperature and time of the first crosslinking reaction, especially the reaction temperature. If the reaction temperature is too low, the activation energy of the first crosslinking agent reaction will be insufficient; if the reaction temperature is too high, it will easily cause the molecular chains of amino-containing compounds to break. Specifically, the reaction temperature of the first crosslinking reaction can be 65℃-95℃. For example, 65℃, 75℃, 85℃ or 95℃, but not limited to the listed values, other unlisted values within the range are also applicable. The reaction time of the first crosslinking reaction can be 25 min-35 min.
[0040] In step (2), the cationic membrane is a homogeneous cationic membrane, and its specific composition is not particularly limited. Any cationic membrane commonly used in the art can be used, such as polyolefin membrane, polysulfone membrane, polyethersulfone membrane, polyacrylonitrile membrane, etc. Preferably, the homogeneous cationic membrane can be a polyolefin membrane or a polyethersulfone membrane.
[0041] In step (2), the coating method can be any coating method commonly used in the art for film surface modification, such as brush coating, dip coating, immersion coating, electrophoretic deposition, spray coating, microgravure coating, slot extrusion coating or scraping coating, etc.
[0042] In step (2), before coating the prepolymer solution onto the surface of the cationic base film, the following steps may also be included: Pretreatment of the cationic membrane.
[0043] The pretreatment process can involve sequentially ultrasonically cleaning the cationic membrane, immersing it in sodium chloride solution, and rinsing it with deionized water.
[0044] Ultrasonic cleaning can remove impurities, debris, and unreacted monomers from the surface of cationic base films by vibration. The cleaning solution used for ultrasonic cleaning can be deionized water or ethanol.
[0045] Soaking in sodium chloride solution can effectively remove residual inorganic salt ions from the surface of cation-based membranes. The sodium chloride solution can have a mass fraction of 5%-10%, and the soaking time can be 24-48 hours.
[0046] Step (3): Immerse the primary crosslinking membrane in a solution containing a secondary crosslinking agent to carry out a second crosslinking reaction, and obtain a monovalent selective cation separation membrane.
[0047] In step (3), the primary crosslinking membrane is modified by secondary crosslinking to achieve ion selectivity, resulting in a monovalent selective cation separation membrane. Aldehyde crosslinking agents can react with amino-containing compounds to form relatively dense and suitable pores on the surface of the modified layer. Through spatial sieving, magnesium ions can be intercepted while lithium ions pass through. In this application, the first crosslinking agent mainly functions to fix the amino-containing compounds onto the cation-based membrane, making the modified layer contain charged groups and ensuring its stability and resistance to detachment. The second crosslinking agent mainly functions to adjust the pore size and number of pores in the modified layer. The ion selectivity of the monovalent selective cation separation membrane in this application is mainly achieved through electrostatic repulsion and pore sieving. Because the modified layer contains charged groups, the inner wall surface of the pores is positively charged, resulting in enhanced electrostatic repulsion of high-valence cations.
[0048] The second crosslinking agent may include any one or a combination of at least two of the following: aldehyde crosslinking agents, isocyanate crosslinking agents, silane crosslinking agents, metal chelate crosslinking agents, or natural polyphenol crosslinking agents.
[0049] In this application, the second crosslinking agent is preferably an aldehyde crosslinking agent, which can be any one or a combination of at least two of 3-chloropropionaldehyde, glutaraldehyde, glyoxal, formaldehyde or succinaldehyde.
[0050] The solution containing the second crosslinking agent includes the second crosslinking agent and deionized water. In the solution containing the second crosslinking agent, the mass percentage of the second crosslinking agent can be 0.1%–0.5%, for example, 0.1%, 0.2%, 0.3%, 0.4% or 0.5%, but is not limited to the listed values; other unlisted values within the range are also applicable.
[0051] In step (3), the reaction time for the second crosslinking reaction can be 20 min - 25 min, for example, 20 min, 22 min, 24 min, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0052] In step (3), the reaction temperature for the second crosslinking reaction is room temperature. Room temperature refers to 20℃-30℃.
[0053] Preferably, after step (3), the following steps may also be included: Step (4): Post-processing.
[0054] Specifically, the post-processing process is as follows: The monovalent selective cation separator was immersed in sodium chloride solution, rinsed with deionized water, and stored in a moist environment.
[0055] In step (4), the mass fraction of sodium chloride solution can be 5%-10%, and the soaking time can be 24 h-48 h.
[0056] In this application, a monovalent selective cation separation membrane is also provided, which is prepared by the above-described method for preparing a monovalent selective cation separation membrane.
[0057] In this application, addressing the long-standing industry pain point of balancing selectivity, stability, and preparation complexity in traditional cation exchange membranes, a novel ternary crosslinking system is proposed: an amino-containing amino compound, a first crosslinking agent (γ-glycidoxypropylmethyldimethoxysilane or epoxy polyethylene glycol), and an aldehyde crosslinking agent. This system achieves a gradient distribution of crosslinking density from the membrane interior to the surface through molecular-level design. During preparation, the amino groups of the amino-containing amino compound undergo a ring-opening reaction with the epoxy groups of the first crosslinking agent to construct an initial crosslinking framework with excellent mechanical strength. Furthermore, the polysiloxane characteristic segments inherent in γ-glycidoxypropylmethyldimethoxysilane spontaneously hydrolyze and condense during crosslinking to form stable Si-O bond microregions. This significantly improves the membrane framework's resistance to hydrolysis and acid / alkali stress, while the flexible siloxane segments adjust the rigidity of the crosslinking network, preventing framework embrittlement and providing better machinability, thus offering a structural basis for subsequent separation operations and long-term operation. Building upon this foundation, aldehyde compounds are further utilized to precisely control the surface charge density and pore size distribution of the membrane. Combined with the controllable in-situ construction of continuous, interconnected sub-nanometer lithium-ion channels, highly efficient selective transport of monovalent lithium ions to multivalent magnesium ions is ultimately achieved. Furthermore, this application simplifies the traditional multi-step crosslinking process into a single-step "coating-immersion" molding process. The reaction conditions are mild and easily controlled, significantly reducing production energy consumption and preparation costs compared to traditional processes. The resulting monovalent selective cation separation membrane possesses excellent mechanical properties, superior ion sieving capabilities, and long-term operational stability, fully meeting the stringent application requirements of high-value ion separation scenarios such as lithium extraction from salt lakes.
[0058] The technical solution provided in this application has at least the following advantages and positive effects: 1. Simultaneous Improvement of Ion Selectivity and Flux: In this application, γ-glycidyl etheroxypropylmethyldimethoxysilane or epoxy polyethylene glycol is selected as the first crosslinking agent. Its inherent epoxy end groups can efficiently undergo ring-opening reactions with amino groups containing amino compounds. The flexible polysiloxane segments inherent in γ-glycidyl etheroxypropylmethyldimethoxysilane or the flexible polyethylene glycol segments inherent in epoxy polyethylene glycol can adjust the rigidity of the crosslinking network, providing a uniform framework for subsequent channel construction. Based on this, an ultrathin selective separation layer (i.e., a modified layer) is constructed under the action of a second crosslinking agent, precisely controlling the surface charge density and pore size distribution. Combined with the in-situ construction of uniformly sized lithium-ion channels, this achieves Li... + / Mg 2+With a separation coefficient as high as 18 (60% higher than traditional membranes), it outperforms existing commercial membranes and meets the requirements for high-efficiency separation.
[0059] 2. Excellent structural and chemical stability, excellent acid and alkali resistance, and wide range of applications: When the first crosslinking agent is γ-glycidoxypropylmethyldimethoxysilane, after the ring-opening reaction of γ-glycidoxypropylmethyldimethoxysilane, its siloxane segments can also be hydrolyzed and condensed in situ to form polysiloxane microdomains containing stable Si-O bonds. A single crosslinking can construct a primary framework that combines rigidity and flexibility, providing strong mechanical support. Subsequent secondary crosslinking further forms a dense selective network, and the dual effect effectively inhibits membrane swelling.
[0060] Thanks to the first crosslinking agent, especially the epoxy crosslinking agent containing siloxane, which forms polysiloxane microdomains and stable Si-O chemical bonds, the modified layer has excellent overall chemical stability and is not easily degraded in extreme environments such as strong acid (pH=1) or strong alkali (pH=13). It can be adapted to various complex working conditions such as salt lake brine and industrial wastewater electrolyte.
[0061] The monovalent selective cation separation membrane of this application has a wet swelling rate as low as 2%–4%, maintains stable operation even under extreme environments of pH 1–13, has a long-term circulating flux decay rate of <5%, and a cycle life of >20 hours, and can be stably adapted to complex working conditions such as salt lake brine.
[0062] 3. Simplified process, green and low carbon: The traditional multi-step cross-linking is simplified into a single-step molding process of "coating-immersion". The low-temperature solution coating technology reduces energy consumption by more than 30% and the number of process steps by more than 50%. There is no harmful solvent emission, which is suitable for large-scale industrial production and reduces manufacturing costs.
[0063] 4. Strong substrate compatibility and broad application prospects: This preparation method is compatible with various homogeneous cationic base membranes such as polysulfone, polyethersulfone, and polyacrylonitrile. The epoxy end groups of the first crosslinking agent can simultaneously bond with the active groups on the surface of the base membrane, making the modified layer more firmly bonded to the base membrane. It is not easy to fall off during long-term operation and can be adapted to electrodialysis separation equipment of different specifications. It is widely used in many fields such as lithium extraction from salt lakes, hard water softening, and electrolyte purification.
[0064] 5. Simple preparation process, easy to scale up industrially: The reaction conditions in this application are mild, requiring no complex equipment or strict reaction control. The entire preparation process is simple to operate and has good repeatability, making it suitable for large-scale industrial production. One of the core innovations is the use of γ-glycidyl etheroxypropylmethyldimethoxysilane or epoxy polyethylene glycol as the first crosslinking agent, especially γ-glycidyl etheroxypropylmethyldimethoxysilane. Its molecule has epoxy end groups that can efficiently undergo ring-opening reactions with amino-modified solvents. Its siloxane segments can be hydrolyzed and condensed in situ to form stable polysiloxane microdomains. No additional rigid reinforcing components are needed, which simplifies the formulation system and improves the stability of the skeleton, further reducing the difficulty of process control for industrial scale-up.
[0065] 6. Low raw material cost and environmentally friendly: The amino-containing compounds, first crosslinking agent, and second crosslinking agent used in this application are widely available and relatively inexpensive. Compared to high-end products such as perfluorosulfonic acid resin-based films, the raw material cost can be reduced by more than 50%. Furthermore, the preparation process does not require the use of toxic or harmful organic solvents, and the reaction waste liquid is easy to treat, making it environmentally friendly and in line with the development concept of green chemistry.
[0066] In summary, this application successfully prepared a monovalent selective cation separation membrane with high selectivity, high ion flux, excellent acid and alkali resistance, and stability by reacting amino-containing compounds with a crosslinking agent. Compared with existing technologies, this application has significant advantages in preparation process, performance stability, applicability, and cost control. It provides an efficient and economical solution for solving the problem of selective separation of cations with different valence states under complex operating conditions and has broad prospects for industrial application.
[0067] The present application will be further described below through specific embodiments.
[0068] Example 1 This embodiment provides a method for preparing a monovalent selective cation separation membrane, the method comprising the following steps: Step (1): Polyethyleneimine with a molecular weight of 10 kDa and triethylenetetramine (mass ratio of 1:2) are mixed and dissolved in deionized water and stirred until transparent. Then, γ-glycidyl etheroxypropylmethyldimethoxysilane crosslinking agent is added to obtain a prepolymer solution.
[0069] In the prepolymer solution, the mass percentage of γ-glycidyl etheroxypropylmethyl dimethoxysilane crosslinking agent is 0.8%, and the mass percentage of amino compounds is 1.2%.
[0070] Step (2): Immerse the cationic base membrane (polypropylene base membrane) in deionized water for ultrasonic cleaning, then immerse it in a 10% sodium chloride solution for 24 hours, and then rinse it with deionized water.
[0071] The prepolymer solution was then coated onto the surface of the cationic base membrane, followed by heating and crosslinking reaction at 90°C for 30 minutes to obtain a single crosslinked membrane.
[0072] Step (3): Immerse the primary cross-linked membrane in a solution containing succinaldehyde and carry out the cross-linking reaction for 20 minutes to form a monovalent selective cation separation membrane.
[0073] The solution containing succinaldehyde consists of deionized water and succinaldehyde; the mass percentage of succinaldehyde in the solution is 0.3%.
[0074] Step (4): Soak the monovalent selective cation separator in a 10% sodium chloride solution for 24 hours, then rinse with deionized water and store it in a moisturizing environment.
[0075] Taking Example 1 as an example, the SEM image of the obtained monovalent selective cation separation membrane at a magnification of 5000X is as follows. Figure 1 As shown, a dense and uniform modified layer was formed on the membrane surface, indicating that the modified layer reacted successfully on the cationic base membrane.
[0076] Example 2 This embodiment provides a method for preparing a monovalent selective cation separation membrane, the method comprising the following steps: Step (1): Polyethyleneimine with a molecular weight of 10 kDa and triethylenetetramine (mass ratio of 1:1) are dissolved in deionized water and stirred until transparent. Then, γ-glycidyl etheroxypropylmethyldimethoxysilane crosslinking agent is added to obtain a prepolymer solution.
[0077] In the prepolymer solution, the mass percentage of γ-glycidyl etheroxypropylmethyl dimethoxysilane crosslinking agent is 0.8%, and the mass percentage of amino compounds is 1.2%.
[0078] Step (2): Immerse the cationic base membrane (polypropylene base membrane) in deionized water for ultrasonic cleaning, then immerse it in a 10% sodium chloride solution for 24 hours, and then rinse it with deionized water.
[0079] The prepolymer solution was then coated onto the surface of the cationic base membrane, followed by heating and crosslinking reaction at 90°C for 30 minutes to obtain a single crosslinked membrane.
[0080] Step (3): Immerse the primary cross-linked membrane in a solution containing succinaldehyde and carry out the cross-linking reaction for 20 min to obtain a monovalent selective cation separation membrane.
[0081] The solution containing succinaldehyde consists of deionized water and succinaldehyde; the mass percentage of succinaldehyde in the solution is 0.3%.
[0082] Step (4): Soak the monovalent selective cation separator in a 10% sodium chloride solution for 24 hours, then rinse with deionized water and store it in a moisturizing environment.
[0083] Example 3 This embodiment provides a method for preparing a monovalent selective cation separation membrane, the method comprising the following steps: Step (1): Polyethyleneimine with a molecular weight of 10 kDa and triethylenetetramine (mass ratio of 1:2) are dissolved in deionized water and stirred until transparent. Then, γ-glycidyl etheroxypropylmethyldimethoxysilane crosslinking agent is added to obtain a prepolymer solution.
[0084] In the prepolymer solution, the mass percentage of γ-glycidyl etheroxypropylmethyldimethoxysilane crosslinking agent is 0.7%, and the mass percentage of amino compounds is 1.2%.
[0085] Step (2): Immerse the cationic base membrane (polypropylene base membrane) in deionized water for ultrasonic cleaning, then immerse it in a 10% sodium chloride solution for 24 hours, and then rinse it with deionized water.
[0086] The prepolymer solution was then coated onto the surface of the cationic base membrane, followed by heating to a crosslinking reaction at 90°C for 30 minutes to obtain a primary crosslinked membrane.
[0087] Step (3): Immerse the primary cross-linked membrane in a solution containing succinaldehyde and carry out the cross-linking reaction for 20 minutes to form a monovalent selective cation separation membrane.
[0088] The solution containing succinaldehyde consists of deionized water and succinaldehyde; the mass percentage of succinaldehyde in the solution is 0.3%.
[0089] Step (4): Soak the monovalent selective cation separator in a 10% sodium chloride solution for 24 hours, then rinse with deionized water and store it in a moisturizing environment.
[0090] Example 4 This embodiment provides a method for preparing a monovalent selective cation separation membrane, the method comprising the following steps: Step (1): Polyethyleneimine with a molecular weight of 10 kDa and triethylenetetramine (mass ratio of 1:2) are dissolved in deionized water and stirred until transparent. Then, γ-glycidyl etheroxypropylmethyldimethoxysilane crosslinking agent is added to obtain a prepolymer solution.
[0091] In the prepolymer solution, the mass percentage of γ-glycidyl etheroxypropylmethyl dimethoxysilane crosslinking agent is 0.8%, and the mass percentage of amino compounds is 1.2%.
[0092] Step (2): Immerse the cationic base membrane (polypropylene base membrane) in deionized water for ultrasonic cleaning, then immerse it in a 10% sodium chloride solution for 24 hours, and then rinse it with deionized water.
[0093] The prepolymer solution was then coated onto the surface of the cationic base membrane, followed by heating to a crosslinking reaction at 90°C for 30 minutes to obtain a primary crosslinked membrane.
[0094] Step (3): Immerse the primary cross-linked membrane in a solution containing succinaldehyde and carry out the cross-linking reaction for 20 minutes to form a monovalent selective cation separation membrane.
[0095] The solution containing succinaldehyde consists of deionized water and succinaldehyde; the mass percentage of succinaldehyde in the solution is 0.2%.
[0096] Step (4): Soak the monovalent selective cation separator in a 10% sodium chloride solution for 24 hours, then rinse with deionized water and store it in a moisturizing environment.
[0097] Example 5 This embodiment provides a method for preparing a monovalent selective cation exchange membrane. Compared with Example 1, the only difference is that the molecular weight of polyethyleneimine is changed to 70 kDa in step (1).
[0098] Example 6 This embodiment provides a method for preparing a monovalent selective cation exchange membrane. Compared with Example 1, the only difference is that in step (1), γ-glycidoxypropylmethyldimethoxysilane is replaced with epoxy polyethylene glycol.
[0099] Example 7 This embodiment provides a method for preparing a monovalent selective cation exchange membrane. Compared with Example 1, the only difference is that in step (1), polyethyleneimine with a molecular weight of 10 kDa and triethylenetetramine (mass ratio of 1:4) are mixed and dissolved in deionized water.
[0100] Example 8 This embodiment provides a method for preparing a monovalent selective cation exchange membrane. Compared with Example 1, the only difference is that in step (1), the mass percentage of γ-glycidyl etheroxypropylmethyl dimethoxysilane crosslinking agent in the prepolymer solution is 1.0%.
[0101] Example 9 This embodiment provides a method for preparing a monovalent selective cation exchange membrane. Compared with Example 1, the only difference is that in step (3), the mass percentage of succinyl aldehyde in the solution containing succinyl aldehyde is 0.5%.
[0102] Comparative Example 1 This comparative example provides a method for preparing a monovalent selective cation exchange membrane. The only difference from Example 1 is that the first crosslinking agent (γ-glycidoxypropylmethyldimethoxysilane crosslinking agent) is not added to the prepolymer solution in step (1).
[0103] Taking Comparative Example 1 as an example, the SEM image of the obtained selective cation exchange membrane at a magnification of 5000X is as follows. Figure 2 As shown.
[0104] Comparative Example 2 This comparative example provides a method for preparing a monovalent selective cation exchange membrane. Compared with Example 1, the only difference is that step (3) is not performed, that is, the selective cation exchange membrane is obtained by cross-linking the membrane once.
[0105] Taking Comparative Example 2 as an example, the SEM image of the obtained selective cation exchange membrane at a magnification of 5000X is as follows. Figure 3 As shown.
[0106] Comparative Example 3 This comparative example provides a method for preparing a monovalent selective cation exchange membrane, which differs from Example 1 only in that the heating temperature in step (2) is 60°C.
[0107] Comparative Example 4 This comparative example provides a method for preparing a selective cation exchange membrane. The only difference from Example 1 is that in step (1), the mass percentage of amino compounds in the prepolymer solution is 1.4%.
[0108] Comparative Example 5 This comparative example provides a method for preparing a monovalent selective cation exchange membrane. Compared with Example 1, the only difference is that in step (3), the crosslinking reaction is carried out for 30 minutes.
[0109] Performance testing: The test was conducted using a simulated brine solution from a salt lake, with lithium at 0.6 g / L and magnesium at 12 g / L. The electrochemical apparatus used heterogeneous anion exchange membranes at both electrodes, with the test membrane placed in the middle; the effective membrane area was 19.6 cm². 2 100 A / m constant current 2The test was run for 2 hours. The dilute chamber contained 1-3 L of a mixed solution of 0.1 mol / L LiCl and 0.5 mol / L MgCl2; the concentrate chamber contained 300 mL of 0.02 mol / L LiCl solution; and the anode and cathode chambers contained 1 L of 0.5 mol / L NaCl solution. The conductivity and temperature of the concentrate chamber and the pH of the dilute chamber were recorded every 10 min. After 2 hours, a 10 mL sample from the concentrate chamber was taken for ICP analysis.
[0110] The selective separation performance of the membrane is tested by the ion selectivity coefficient ( ). Characterization, in which lithium-ion flux ( ), magnesium ion flux ( ), ion selectivity coefficient ( The specific calculation is performed using the following formula: ; ; ; Where A, V, and t are the effective membrane areas (m², t ... 2 ), concentration chamber volume (L) and operating time (h). C t Li and C0 Li The values represent the Li ion concentrations (mol / L) in the concentration chamber at runtime t and the initial time, respectively. t Mg and C0 Mg The values represent the Li ion concentrations (mol / L) in the concentration chamber at running time t and at the initial time, respectively. and The values represent the initial Li concentration (mol / L) and the initial Mg concentration (mol / L) in the dilute chamber, respectively.
[0111] The monovalent selective cation separation membranes prepared in Examples 1-5 and Comparative Examples 1-5 were subjected to the above-mentioned performance tests, and the results are shown in Table 1.
[0112] Table 1
[0113] As can be seen from the data in Table 1: (1) As can be seen from the data in Example 1, the monovalent selective cation separation membrane provided in this application achieves a lithium flux of 2.1 mol / (m under optimal conditions. 2 The ion selectivity is as high as 18.01 (around h).
[0114] (2) As can be seen from the data of Examples 1 and Examples 2-4, Examples 2, 3, and 4 only adjusted a single variable, changing the ratio of amino-containing compounds, the mass ratio of the first crosslinking agent, and the mass ratio of the second crosslinking agent, respectively. However, the final measured lithium flux and ion selectivity were all inferior to those of Example 1. The reason for this result is that if the compound ratio of amino-containing compounds is unbalanced, it will lead to a decrease in the uniformity of the distribution of pore structure inside the modified layer; and when the mass ratio of the first or second crosslinking agent deviates from the optimal value, it will cause insufficient crosslinking modification reaction, resulting in an increase in the number of pores in the modified layer and difficulty in accurately controlling the pore size. Ultimately, this leads to damage to the ion transport channels, reducing the lithium ion transport efficiency and weakening the selective interception ability of divalent ions.
[0115] The difference between Example 5 and Example 1 lies in the use of high molecular weight amino-containing compounds with different molecular weights. According to the test results, Example 1 is a preferred combination of amino-containing compounds with different molecular weights, which allows for precise control of the pore size and distribution of the channels at the molecular level, ultimately resulting in more uniform and continuously connected regular lithium-ion transport channels.
[0116] (3) Comparing the experimental data of Example 1 with those of Comparative Examples 1-5, it can be seen that Comparative Examples 1-5 are all single-variable control experiments. The variables are: no first crosslinking agent added, no second crosslinking agent added, changing the reaction temperature, adjusting the mass ratio of amino compounds, and changing the reaction time of the second crosslinking.
[0117] (4) Comparing the experimental data of Example 1 with those of Examples 6-8, it can be seen that: in Example 6, the first crosslinking agent was replaced with epoxy polyethylene glycol, and the modification effect of Example 6 was basically the same as that of Example 1, with excellent lithium flux and ion selectivity; in Example 7, the ratio of small molecule amino compounds was increased, and it was found that it was easy to over-modify, resulting in a decrease in lithium flux; through the experimental results of Examples 7 and 8, it can be seen that when the mass percentage of the first crosslinking agent or the second crosslinking agent is increased, it is easy to cause the surface of the modified layer to become too dense, resulting in a decrease in lithium flux. Although the ion selectivity coefficient is between 9 and 12, it does not meet the production requirements.
[0118] Comparing Example 1 with Comparative Examples 1-2, it is evident that when any key condition in Example 1 is omitted, the lithium flux and ion selectivity coefficient of the modified membrane both show a significant decrease. In this application, the ternary synergistic effect of the first crosslinking agent, the second crosslinking agent, and amino-containing compounds of different molecular weights is the core of constructing the modified layer of regular ion transport channels: γ-glycidoxypropylmethyldimethoxysilane, as the first crosslinking agent, has epoxy reaction end groups, which can efficiently undergo ring-opening reactions with the amino groups of amino-containing compounds. Its inherent polysiloxane segments can also undergo in-situ hydrolysis and condensation to form stable microdomains, providing a basic framework with both rigidity and flexibility for the initial crosslinking network; the second crosslinking agent further optimizes the density and uniformity of the crosslinking network by reacting with the residual active groups of the framework.
[0119] Compared with Comparative Examples 3-5, Example 1 shows that lowering the reaction temperature, increasing the concentration of amino compounds, or extending the duration of the secondary crosslinking reaction all lead to a decrease in lithium flux.
[0120] Specifically, a loose structure is prone to non-selective porosity, leading to an increase in magnesium flux and a decrease in lithium flux; an excessively high concentration of amino compounds will cause excessive cross-linking, making the modified layer too dense, excessively compressing the lithium ion transport channels, and increasing transport resistance; and an excessively long secondary cross-linking reaction will promote excessive cross-linking, triggering side reactions that lead to acid production on the surface of the modified film, destroying the stability of the ion transport channels, and ultimately reducing lithium flux.
[0121] The monovalent selective cation separation membranes prepared in Example 1 and Comparative Example 1 were tested for acid and alkali resistance. The results are shown in Table 2.
[0122] The monovalent selective cation separator membranes were immersed in neutral solution (i.e., the salt solution in Table 1), strong acid solution, and strong alkali solution at room temperature for 48 hours, respectively, before the above performance tests were performed. The pH values of the neutral solution and acidic solution were 7, 1, and 13, respectively.
[0123] Table 2
[0124] As can be seen from the data in Table 2: (1) The test data from Example 1 show that the monovalent selective cation exchange membrane prepared by stepwise modification with the first crosslinking agent and the second crosslinking agent did not show significant changes in lithium flux and ion selectivity after being soaked in neutral, strong acid and strong alkali solutions for 48 hours, respectively, and the stability performance was excellent.
[0125] (2) Comparison with the test results of Comparative Example 1: When only the second crosslinking agent is used for modification and the first crosslinking agent γ-glycidyl etheroxypropylmethyldimethoxysilane is not added, the membrane loses its ion selectivity after only two tests under neutral conditions, and the modified layer has already peeled off; while after soaking in strong acid or strong alkali, the peeling of the modified layer is significantly aggravated, and the membrane completely loses its ion selectivity.
[0126] (3) Based on the test results of Example 1 and Comparative Example 1, it can be inferred that after the ring-opening reaction of the epoxy group of γ-glycidoxypropylmethyldimethoxysilane, the siloxane segments in the molecule can be hydrolyzed and condensed in situ to form polysiloxane microdomains containing stable Si-O bonds; the primary framework with both rigidity and flexibility can be constructed through the first crosslinking step, providing stable and strong mechanical support for the entire membrane system. Subsequent secondary crosslinking can further form a dense ion-selective network. This double crosslinking structural design can effectively suppress the swelling effect of the membrane in the aqueous environment and can still operate stably in extreme environments with a wide pH range of pH 2 to 12.
[0127] The monovalent selective cation separation membrane prepared in Example 1 was subjected to a stability test. The monovalent selective cation separation membrane was cycled for 8 times to perform the above performance test. The results of each test are shown in Table 3.
[0128] Table 3
[0129] As shown in Table 3, the monovalent selective cation separation membrane prepared in Example 1 exhibits excellent long-term cycling stability. After eight consecutive separation cycles, the lithium-ion flux can still be maintained at 96% of the initial value, proving that its structure is not easily damaged during repeated use and can maintain ion transport efficiency and separation selectivity stably for a long time. This outstanding performance advantage stems from the specific dual crosslinking synergistic mechanism of this application: the amino group in the amino-containing compound first undergoes a ring-opening reaction with the epoxy group of the first crosslinking agent γ-glycidoxypropylmethyldimethoxysilane to generate stable covalent carbon-nitrogen bonds. At the same time, the siloxane segments of γ-glycidoxypropylmethyldimethoxysilane undergo in-situ hydrolysis and condensation to form polysiloxane microdomains containing stable Si-O bonds, which together construct an initial crosslinking framework with both mechanical strength and chemical stability. The amino group remaining on the framework then undergoes a Schiff base condensation reaction with the aldehyde group of the second crosslinking agent, further promoting the densification of the surface modified layer. The synergistic effect of double crosslinking: the initial framework provides stable structural support, and the secondary crosslinking enhances network density and chemical stability, which can effectively resist the damage to the membrane structure caused by swelling, hydrolysis or mechanical stress during long-term cycling, fundamentally avoiding the collapse or abnormal expansion of lithium-ion channels, and ultimately achieving long-term stable maintenance of lithium flux and separation selectivity.
[0130] It should be understood that the application of this application is not limited to the examples above. Those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of this application.
Claims
1. A method for preparing a monovalent selective cation separation membrane, characterized in that, Includes the following steps: Step (1): Mix deionized water, amino-containing compound and first crosslinking agent to obtain prepolymer solution; Step (2): The prepolymer solution is coated onto the surface of the cationic base membrane to carry out the first crosslinking reaction, thereby obtaining a primary crosslinked membrane; Step (3): Place the primary crosslinking membrane in a solution containing a second crosslinking agent to carry out a second crosslinking reaction, thereby obtaining the monovalent selective cation separation membrane; The first crosslinking agent is γ-glycidyl oxypropyl methyl dimethoxysilane or epoxy polyethylene glycol.
2. The method for preparing a monovalent selective cation separation membrane according to claim 1, characterized in that, In the prepolymer solution, the mass percentage of the amino-containing compound is 1.0%-1.2%; Preferably, the amino-containing compounds include high molecular weight amino-containing compounds and low molecular weight amino-containing compounds; Preferably, the high molecular weight amino-containing compound has a molecular weight ≥5000 Da, and the low molecular weight amino-containing compound has a molecular weight range of <5000 Da. Preferably, the molecular weight of the high molecular weight amino-containing compound is 5000-100000 Da; Preferably, the molecular weight of the high molecular weight amino-containing compound is 10,000-100,000 Da; Preferably, the molecular weight of the low molecular weight amino-containing compound is ≤1800 Da.
3. The method for preparing a monovalent selective cation separation membrane according to claim 2, characterized in that, The mass ratio between the high molecular weight amino-containing compound and the low molecular weight amino-containing compound is 1:1 to 1:4; Preferably, the high molecular weight amino-containing compound is one or a mixture of two of polyethyleneimine and chitosan; Preferably, the low molecular weight amino-containing compound is one or a mixture of two or more of triethylamine, ethylenediamine, and triethylenetetramine; Preferably, the high molecular weight amino-containing compound is polyethyleneimine, and the molecular weight of the polyethyleneimine is 9kDa-11kDa; Preferably, the low molecular weight amino-containing compound is triethylenetetramine.
4. The method for preparing a monovalent selective cation separation membrane according to claim 1, characterized in that, In the prepolymer solution, the mass percentage of the first crosslinking agent is 0.70%–1.0%.
5. The method for preparing a monovalent selective cation separation membrane according to claim 1, characterized in that, In the solution containing the second crosslinking agent, the mass percentage of the second crosslinking agent is 0.1%–0.5%; Preferably, the second crosslinking agent includes any one or a combination of at least two of the following: aldehyde crosslinking agents, isocyanate crosslinking agents, silane crosslinking agents, metal chelate crosslinking agents, or natural polyphenol crosslinking agents. Preferably, the second crosslinking agent is an aldehyde crosslinking agent; Preferably, the second crosslinking agent is one or a combination of two or more of 3-chloropropionaldehyde, glutaraldehyde, glyoxal, formaldehyde or succinaldehyde; Preferably, the second crosslinking agent is butyraldehyde.
6. The method for preparing a monovalent selective cation separation membrane according to claim 1, characterized in that, The reaction temperature for the first crosslinking reaction is 65℃-95℃, and the reaction time is 25 min-35 min. Preferably, the reaction time for the second crosslinking reaction is 20 min - 25 min.
7. The method for preparing a monovalent selective cation separation membrane according to claim 1, characterized in that, In step (2), prior to the step of coating the prepolymer solution onto the surface of the cationic base film, the following steps are also included: The cationic membrane is pretreated; Preferably, the pretreatment process involves sequentially performing ultrasonic cleaning, sodium chloride solution immersion, and deionized water rinsing on the cationic membrane. Preferably, the cleaning solution used in the ultrasonic cleaning is deionized water or ethanol; Preferably, the sodium chloride solution soaking is performed in a sodium chloride solution with a mass ratio of 5%-10% for 24 h-48 h.
8. The method for preparing a monovalent selective cation separation membrane according to claim 1, characterized in that, Following step (3), the following steps are also included: Step (4): Post-processing; Preferably, the post-processing involves immersing the monovalent selective cation separator in a sodium chloride solution, rinsing it with deionized water, and storing it while keeping it moist. Preferably, in step (4), the mass concentration of the sodium chloride solution is 5%-10%, and the soaking time is 24 h-48 h.
9. The method for preparing a monovalent selective cation separation membrane according to claim 1, characterized in that, The cationic membrane is a homogeneous cationic membrane; Preferably, the cationic membrane is a polyolefin-based membrane, a polysulfone-based membrane, a polyethersulfone-based membrane, or a polyacrylonitrile-based membrane; Preferably, the cationic base membrane is a polyolefin base membrane or a polyethersulfone base membrane.
10. A monovalent selective cation separation membrane prepared by the method for preparing a monovalent selective cation separation membrane according to any one of claims 1-9.